Meningkatkan Hasil Belajar Tolak Peluru Gaya Ortodok (Menyamping) melalui Pendekatan Bermain di Kelas V MI Ma’arif Tempursari Tambakboyo Mantingan Ngawi - Misbathul Taufik Hidayah; Aba Sandi Prayoga; Kuncoro Darumoyo (Tamilis Synex: Multidimensional Collaboration, 2025)
The problem in this study is whether the play approach can improve the learning outcomes of orthodox style shot put (sideways) in grade V students of MI Ma`arif Tempursari. The purpose of this study is to improve the learning outcomes of orthodox style shot put (sideways) in grade V students of MI Ma`arif Tempursari. This study is a Classroom Action Research (CAR) consisting of 3 cycles, namely pre-cycle, cycle I, and cycle II. Each cycle consists of 3 stages, namely planning, action, closing. The data collection method used in this study is from the results of test observations on grade V students. The results of the pre-cycle research have not yet obtained results above the KKM, so in Cycle I the results were 72% or 28 students achieved the KKM score and 28% or 11 students did not meet the KKM score. While in cycle II the results improved, namely 85% or 34 students achieved the KKM score and 15% or 5 students did not achieve the KKM score. Based on research results, it was found that the use of play in orthodox (sideways) shot put learning can improve student learning outcomes, student enthusiasm, and a pleasant classroom atmosphere, as well as improving grades.